The stage director's prompt book : a guide to creating and using the stage director's most powerful rehearsal and production tool - Ferreira, Leslie (New York, NY : Routledge, 2023)
"The Stage Director's Prompt Book is a step-by-step, detailed guide on how to create a practical and powerful rehearsal and performance tool - the director's prompt book. A prompt book is a coordinating and organizational tool for the stage director. This book systematizes the creative process the director uses to analyze and interpret a play and coordinates all director-related rehearsal and production activities into a single, self-contained interpretive and organizational system. The book guides the director through the necessary steps and stages of creating and using a prompt book-from play analysis and interpretation, through the formation of a dynamic and theatrical director's vision, to a unique method of physicalizing a play in production. A prompt book of a one-act play is included in the book as a complete example of the system. Such techniques as redlining, color coding and creating a three-column left-hand page are vividly illustrated for readers, allowing them to assemble their own prompt books. In a clear and example-driven format, The Stage Director's Prompt Book offers a system of directorial interpretation that takes the director through a series of point-by point instructions to construct a strong, effective and creative instrument for success. For the undergraduate and graduate student of theatre directing, stage management and producing courses, along with aspiring professional directors, this book provides an interactive and intuitive approach to personalize the stage directing experience and assemble a graphically dynamic and creative director's prompt book"--
A director's glossary (in order of appearance) -- The mechanics of it all : constructing the prompt book -- Redlining the script : finding the important, distilling the essence -- Director's units -- Color coding -- The three column left-hand page -- The right-hand page -- Using the prompt book to schedule and organize for artistic success -- The director and the stage manager -- Four one-hundredths : a model one act -- Final thoughts.
Includes index.
Keywords: Promptbooks; Theater -- Production and direction -- Handbooks, manuals, etc; PERFORMING ARTS / Theater / Direction & Production; PERFORMING ARTS / Theater / Stagecraft; PERFORMING ARTS / Television / Direction & Production